Evaluation of iron, copper and zinc concentrations in commercial foods formulated for healthy cats. Issue 4 (April 2022) - Summers, Stacie; Stockman, Jonathan; Larsen, Jennifer A
Objectives: The aim of this study was to analyze iron, copper and zinc concentrations in commercial foods and compare among food formats (dry, canned, raw), foods marketed by age category (adult 1+ years and senior 7+ years) and foods intended for adult maintenance vs all life stages. Methods: In total, 112 commercial non-therapeutic food products marketed for healthy adult and senior cats were purchased in the USA. Foods were analyzed for their proximate composition. Trace mineral concentrations were measured using inductively coupled argon plasma–optical emission spectroscopy and described on a calculated metabolizable energy basis using standard modified Atwater values. Results: Measured iron (median 58.4 mg/1000 kcal [range 15.7–379.0]), copper (median 5.6 mg/1000 kcal [range 0.8–13.3]) and zinc (median 47.6 mg/1000 kcal [range 7.6–128.1]) concentrations were highly variable among cat foods. When all food products – regardless of their nutritional adequacy substantiation method – were compared with the Association of American Feed Control Officials regulatory minimums, 13/112 food products had a mineral deficiency, of which a majority (n = 11/13) were raw food products. Raw foods had significantly lower trace mineral concentrations compared with dry food products and, except for copper, canned food products. Cat foods marketed for senior cats had higher iron ( P  = 0.019) and zinc ( P <0.0001) concentrations than foods marketed for adult cats. Foods intended for adult maintenance had higher iron ( P  = 0.003) and zinc concentrations than foods intended for all life stages ( P <0.0001). Conclusions and relevance: Iron, copper and zinc concentrations in commercial non-therapeutic foods for adult and senior cats are highly variable. A minority of foods – mainly raw food products – were deficient in these minerals. It is unknown if some foods with high trace mineral concentrations could have adverse effects as studies are needed to establish safe upper limits for dietary intake of trace minerals in healthy cats.